2019
DOI: 10.26508/lsa.201900346
|View full text |Cite
|
Sign up to set email alerts
|

XIAP controls RIPK2 signaling by preventing its deposition in speck-like structures

Abstract: The receptor interacting serine/threonine kinase 2 (RIPK2) is essential for linking activation of the pattern recognition receptors NOD1 and NOD2 to cellular signaling events. Recently, it was shown that RIPK2 can form higher order molecular structures in vitro. Here, we demonstrate that RIPK2 forms detergent insoluble complexes in the cytosol of host cells upon infection with invasive enteropathogenic bacteria. Formation of these structures occurred after NF-κB activation and depended on the caspase activatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 65 publications
6
51
0
Order By: Relevance
“…Notably, RIPK2 K209R was the only form of RIPK2 which seemed to present in a second, higher molecular weight band after stimulation, similar to recently described Riposomes (Ellwanger et al , 2019). To test the impact of each individual modified site on the ubiquitination pattern on RIPK2 during NOD signaling, cells were subjected to UBA pulldowns and analyzed by Western blot.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Notably, RIPK2 K209R was the only form of RIPK2 which seemed to present in a second, higher molecular weight band after stimulation, similar to recently described Riposomes (Ellwanger et al , 2019). To test the impact of each individual modified site on the ubiquitination pattern on RIPK2 during NOD signaling, cells were subjected to UBA pulldowns and analyzed by Western blot.…”
Section: Resultssupporting
confidence: 81%
“…In recent studies, higher order intracellular signaling platforms consisting of RIPK2 and NOD receptors were described (Gong et al , 2018; Pellegrini et al , 2018; Ellwanger et al , 2019). In particular, inhibition of XIAP by either siRNA or by SMAC mimetic compounds led to RIPK2‐containing speck‐like structures in cells, termed Riposomes (Ellwanger et al , 2019). Here, we described two mutations that perturbed the interaction between RIPK2 and XIAP.…”
Section: Resultsmentioning
confidence: 99%
“…RIPK2 signaling may also be regulated via the formation of RIPosomes, which are high molecular weight cytoplasmic complexes comprised of RIPK2 [ 199 , 200 ]. Ellwanger et al [ 199 ] showed RIPosomes form post-NF-κB activation, and suggest that sequestration of RIPK2 in these complexes may act to dampen RIPK2 signaling. Intriguingly, RIPosomes form in the cytosol of epithelial cells upon invasion with S. flexneri , suggesting the pathogen may actively prevent RIPK2 signaling via an unknown process.…”
Section: Ripk2 Signaling In Pathogen Infectionmentioning
confidence: 99%
“…Intriguingly, RIPosomes form in the cytosol of epithelial cells upon invasion with S. flexneri , suggesting the pathogen may actively prevent RIPK2 signaling via an unknown process. Given that inhibition of XIAP was shown to promote deposition of RIPK2 in RIPosomes, it may be that Shigella encodes a virulence factor that targets XIAP for cleavage or degradation, or actively inhibits XIAP-designated sites of ubiquitylation on RIPK2 to inhibit inflammatory signaling [ 199 ].…”
Section: Ripk2 Signaling In Pathogen Infectionmentioning
confidence: 99%
“…Recent studies also re-raised questions about the importance of the regulatory autophosphorylation sites S176 and Y474. Overexpression of RIPK2 mutants in HeLa cells showed that wild-type RIPK2 and the S176A mutant resulted in similar amounts of cytokines following infections with S. flexneri , while the S176E mutant resulted in reduced cytokine levels (Ellwanger et al, 2019). In contrast, cytokine production was completely abolished in cells expressing the RIPK2 Y474F mutant.…”
Section: Ripk2 the Mediator Of Nod Signalingmentioning
confidence: 99%